2021
DOI: 10.3390/v13040665
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Responses to Seoul Orthohantavirus in Experimentally and Naturally Infected Brown Rats (Rattus norvegicus)

Abstract: To clarify the mechanism of Seoul orthohantavirus (SEOV) persistence, we compared the humoral and cell-mediated immune responses to SEOV in experimentally and naturally infected brown rats. Rats that were experimentally infected by the intraperitoneal route showed transient immunoglobulin M (IgM) production, followed by an increased anti-SEOV immunoglobulin G (IgG) antibody response and maturation of IgG avidity. The level of SEOV-specific cytotoxic T lymphocytes (CTLs) peaked at 6 days after inoculation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The detection of high viral RNA copy numbers in genome-positive rodent tissues suggests a high possibility of shedding viruses in their excreta. Yasuda et al reported that the Seoul orthohantavirus was excreted in feces when showing more than 10 5 genome copies/mg of lung tissues of R. norvegicus [ 43 ]. The Lanka virus and SA108 may pose elevated risks of human infections.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of high viral RNA copy numbers in genome-positive rodent tissues suggests a high possibility of shedding viruses in their excreta. Yasuda et al reported that the Seoul orthohantavirus was excreted in feces when showing more than 10 5 genome copies/mg of lung tissues of R. norvegicus [ 43 ]. The Lanka virus and SA108 may pose elevated risks of human infections.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that later during acute infection in rats, the virus-induced endothelial PD-L1 increases to high levels to eliminate virus with minimal collateral vascular and tissue damage in the lungs. When virus is not entirely cleared, this results in persistent infection, as previously observed in naturally infected rats [ 50 ]. The association of severe HRFS cases with increased CD8 + T cell activity and initial failure to mount strong T cell responses early during acute infection, further confirms that the in rats observed PD-L1-mediated immunomodulatory mechanism is less efficient or less present in human patients, thereby failing to protect them from immunopathology [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 72%
“…Conversely, virus specific CD8+ T cells are also effective in recovery [ 24 ]. Suppression of CD8+ T cells is probably associated with the establishment of persistent infection [ 45 , 46 ]. Since KHF, especially KHF5, replicates faster in mouse tissues than prototype Hantaan virus strain 76–118, T-cell activations tending towards increasing inflammation rather than recovery.…”
Section: Discussionmentioning
confidence: 99%